LEDOR: aquele que dá sonoridade aos textos - ROSÁRIO, Kátia Regina Pereira do (2017)
It analyzes the importance of the reader to the access to information by blind people, before the existence of the electronic programs. This is a qualitative, field-based and descriptive research. A bibliographic survey, theoretical study and discussion of the role of “ledor” and reading for people with visual impairment. As well as were made semi-structured interviews, and the description and analysis of the data collected were used in this study. There were seven participants as subjects of the research, with three lenders and four readers (who are blinds). It is considered that both digital lenders and human lenders are widely used by these users.